Prarancangan Pabrik Biodiesel Dari Crude Palm Oil Dan Metanol Dengan Proses Transesterifikasi Kapasitas 130.000 Ton/Tahun - Mikasasari, Rizky Purnama; , Ibu Emi Erawati, S.T., M.Eng; , Ir. Nur Hidayati, Ph.D (2016)
Indonesia is an oil -producing countries. Due to the limited number of refineries owned for producing fuel oil (BBM), Indonesia had to import fuel to their domestic needs. Biodiesel is a fuel from vegetable oil with a purity of 98%. Biodiesel is designed with a capacity of 130,000 tonnes/year using raw materials palm oil and methanol with NaOH catalyst that operates at a temperature of 60°C and 1 atmosphere of a pressure, the mole ratio CPO : methanol, 1 : 6 with the conversion of 98%. The reaction occurs in two RATB the transesterification process and liquid phase. The reaction was exothermic include cooling coil. The land area required for 7365 m2 and total workforce of 155 people. CPO needs 16342.75 kg/hr, methanol 3.708,02 kg/hr and NaOH catalyst 163.43 kg/hr. The water needs from the Bontang River at 15737.28 kg/h, the diesel fuel 208,01 L/h , the compressed air is 150 m3/h and 521 kW electricity needs . The plant will be build in Bontang, East Kalimantan. The results of economic analysys obtained FCI Rp. 587,128,680,758. MC per year is Rp. 910,236,044,378. Then profits before tax Rp. 139,286,037,645 per year, while profit after tax Rp. 104,464,528,233 per year. Results of Percent ROI before tax of 23.7%, and 17.8% after tax, before tax POT is 2.97 years and 3.60 years after tax . BEP and SDP 54.62% and amounted to 25.93% and 27.59% of DCF. From these evaluations, that Biodiesel is feasible to apply.